The role of end‐diastolic myocardial fibre stretch on infarct extension. (4th December 2019) - Leong, Chin Neng; Dokos, Socrates; Andriyana, Andri; Liew, Yih Miin; Chan, Bee Ting; Abdul Aziz, Yang Faridah; Chee, Kok‐Han; Sridhar, Ganiga Srinivasaiah; Lim, Einly
Abstract: Myocardial infarct extension, a process involving the enlargement of infarct and border zone, leads to progressive degeneration of left ventricular (LV) function and eventually gives rise to heart failure. Despite carrying a high risk, the causation of infarct extension is still a subject of much speculation. In this study, patient‐specific LV models were developed to investigate the correlation between infarct extension and impaired regional mechanics. Subsequently, sensitivity analysis was performed to examine the causal factors responsible for the impaired regional mechanics observed in regions surrounding the infarct and border zone. From our simulations, fibre strain, fibre stress and fibre stress‐strain loop (FSSL) were the key biomechanical variables affected in these regions. Among these variables, only FSSL was correlated with infarct extension, as reflected in its work density dissipation (WDD) index value, with high WDD indices recorded at regions with infarct extension. Impaired FSSL is caused by inadequate contraction force generation during the isovolumic contraction and ejection phases. Our further analysis revealed that the inadequacy in contraction force generation is not necessarily due to impaired myocardial intrinsic contractility, but at least in part, due to inadequate muscle fibre stretch at end‐diastole, which depresses the ability of myocardium to generate adequate contraction force in the subsequent systole (according to the Frank‐Starling law). Moreover, an excessively stiff infarct may cause its neighbouring myocardium to be understretched at end‐diastole, subsequently depressing the systolic contractile force of the neighbouring myocardium, which was found to be correlated with infarct extension. Abstract : This work examined the correlation between infarct extension and left ventricular regional mechanics, including factors leading to the observed impaired mechanics. It was found that fibre stress‐strain loop (FSSL) was the only biomechanical variable that correlated with infarct extension. The impaired FSSL was caused by inadequate contraction force generation during the isovolumic contraction and ejection phases. Inadequate stretch of the myocardium at end‐diastole, in particular with excessively stiff infarct, can contribute to this phenomenon.